2020
DOI: 10.1177/0954409720902359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of track irregularities of high-speed railways on the thermal characteristics of the traction motor bearing

Abstract: The operating temperature plays a key role in the service reliability of ball bearings used in the traction motor of high-speed trains. Studies on the heat generation and temperature distributions of the bearing under the vehicle vibration environment are critical for designing the high-speed train traction motor bearing and to monitor its operation. In this paper, an SKF friction torque model that considers the inlet shear heating reduction and kinematic replenishment/starvation reduction was used to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The single−stage spur gear transmission is widely employed in gear transmissions in locomotives [8][9][10][11][12]21,22,27]. The traction torque generated from the traction motor is transmitted to the wheel-rail interface via the flexible teeth deformation of the gear pair along the line of action which is represented by a spring-damper element (K m , C m ).…”
Section: Mesh Forces Of Gear Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single−stage spur gear transmission is widely employed in gear transmissions in locomotives [8][9][10][11][12]21,22,27]. The traction torque generated from the traction motor is transmitted to the wheel-rail interface via the flexible teeth deformation of the gear pair along the line of action which is represented by a spring-damper element (K m , C m ).…”
Section: Mesh Forces Of Gear Transmissionmentioning
confidence: 99%
“…Chen et al [8] further considered the power transmission path of the locomotive and developed a locomotive−track coupled dynamics model with gear transmissions to research the dynamic responses of the gear transmissions and the influence of the tooth root crack on the whole coupled system. Liu et al [9][10][11] and Wang et al [12], respectively, analyzed the dynamic and thermal characteristics of the motor bearings in the vibration environment of a locomotive or a high−speed train.…”
Section: Introductionmentioning
confidence: 99%
“…The radial force on cylindrical roller bearings of traction motor caused by track irregularities using the vehicle dynamics model established in the SIMPACK software (Wang et al, 2020) is shown in Figure 5.…”
Section: Bearing Load Due To Vehicle Environmentmentioning
confidence: 99%
“…Ge (2016) and Wang et al (2019) analyze the influence of the track irregularity impacts on the dynamical behavior of axle bearing. Wang et al (2020) studied the effect of the track irregularity on the thermal characteristics of traction motor bearing. In this paper, we mainly consider the influence of the track irregularity on the bearing load, and then the thermal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [17] focused on the effect of the system spatial variability on the vehicle-track coupled system using the method of statistics. Huang et al [18] and Wang et al [19], respectively, investigated the dynamic characteristics of the vehicle and the thermal characteristics of the motor bearing using SIMPACK. Based on the typical vehicle-track coupled dynamics model and a calculation method for the time-varying gear mesh stiffness, Chen et al [20] and Liu et al [21] proposed a planar locomotive-track coupled dynamics model considering the detailed traction power transmission path.…”
Section: Introductionmentioning
confidence: 99%